Bentuk Penyajian Tari Tor-Tor Naposo Nauli Bulung pada Upacara Perkawinan Mandailing di Sigantang Kecamatan Ranah Batahan Kabupaten Pasaman Barat - Syarah, Sisri; Nerosti, Nerosti (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of preserving traditional performing arts within the context of customary ceremonies, specifically Tari Tor-Tor Naposo Nauli Bulung, which forms part of the wedding rituals of the Mandailing community in Sigantang, Ranah Batahan Subdistrict, West Pasaman Regency. The research aims to describe and analyze the presentation form of this dance within the context of marriage ceremonies. A qualitative approach with a descriptive-analytical method was employed. Primary and secondary data were collected through literature review, observation, interviews, and documentation, and subsequently analyzed through the stages of data collection, description, identification, and reporting. The findings indicate that Tari Tor-Tor Naposo Nauli Bulung consists of eight movement variations, categorized into pure movements, such as jonjong, siamun, siambirang, tujolo, and the opening sequence and meaningful movements like maido tutuhan, symbolizing a prayer for a smooth ceremony, and mijur, marking the formalization of the marriage. The dance employs floor patterns that are horizontal, spiral, and circular. The accompanying music includes gondang, gong, momongan, suling, and tulilla. Dancers wear simple traditional attire, with a formation of five men and five women, and use a traditional selendang as the main prop. The performance takes place in the bride’s courtyard and serves as entertainment, a symbol of unity, a gesture of respect for elders, and a medium for preserving the social and cultural values of the Mandailing people.